(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
The purpose of this study is to describe the frequency of potential drug prescribing omissions (PPOs) for elderly patients at the time of hospital discharge and to compare the frequency PPOs among different medical specialities. This cross-sectional study examined data from elderly patients when they were admitted for >24 h to a northeastern Brazil teaching hospital during June–December 2016. Were included in the study 227 patients, of whom 36.9% had at least one PPO. The highest number of PPOs was identified among those with at least 5 prescribed drugs. In total, 153 PPOs were identified at hospital discharge. In most cases (78.4%), patients were not evaluated by the specialist physician.The most commonly identified PPOs on discharge were: the omission of statin therapy in cases of diabetes mellitus plus one or more cardiovascular-associated factor; calcium and vitamin D supplements in patients with known osteoporosis; and angiotensin converting enzyme inhibitors in cases of chronic heart failure. The results of this study suggest that the frequency of prescribing omissions PPOs during patient discharge was high. This can be avoided by the careful evaluation by prescribers with experience in certain specialties where several prescribed omissions would be common.